The clinical and molecular spectrum of ZFYVE26-associated hereditary spastic paraplegia: SPG15 - Saffari, Afshin; Kellner, Melanie; Jordan, Catherine; Rosengarten, Helena; Mo, Alisa; Zhang, Bo; Strelko, Oleksandr; Neuser, Sonja Anna; Davis, Marie Y; Yoshikura, Nobuaki; Futamura, Naonobu; Takeuchi, Tomoya; et al. (Brain, 2023)
In the field of hereditary spastic paraplegia (HSP), progress in molecular diagnostics needs to be translated into robust phenotyping studies to understand genetic and phenotypic heterogeneity and to support interventional trials. ZFYVE26-associated hereditary spastic paraplegia (HSP-ZFYVE26, SPG15) is a rare, early-onset complex HSP, characterized by progressive spasticity and a variety of other neurological symptoms. While prior reports, often in populations with high rates of consanguinity, have established a general phenotype, there is a lack of systematic investigations and a limited understanding of age-dependent manifestation of symptoms. Here we delineate the clinical, neuroimaging and molecular features of 44 individuals from 36 families, the largest cohort assembled to date. Median age at last follow-up was 23.8 years covering a wide age range (11-61 years). While symptom onset often occurred in early childhood [median: 24 months, interquartile range (IQR) = 24], a molecular diagnosis was reached at a median age of 18.8 years (IQR = 8), indicating significant diagnostic delay. We demonstrate that most patients present with motor and/or speech delay or learning disabilities. Importantly, these developmental symptoms preceded the onset of motor symptoms by several years. Progressive spasticity in the lower extremities, the hallmark feature of HSP-ZFYVE26, typically presents in adolescence and involves the distal lower limbs before progressing proximally. Spasticity in the upper extremities was seen in 64%. We found a high prevalence of extrapyramidal movement disorders including cerebellar ataxia (64%) and dystonia (11%). Parkinsonism (16%) was present in a subset and showed no sustained response to levodopa. Cognitive decline and neurogenic bladder dysfunction progressed over time in most patients. A systematic analysis of brain MRI features revealed a common diagnostic signature consisting of thinning of the anterior corpus callosum, signal changes of the anterior forceps and non-specific cortical and cerebellar atrophy. The molecular spectrum included 45 distinct variants, distributed across the protein structure without mutational hotspots. Spastic Paraplegia Rating Scale scores, SPATAX Disability Scores and the Four Stage Functional Mobility Score showed moderate strength in representing the proportion of variation between disease duration and motor dysfunction. Plasma neurofilament light chain levels were significantly elevated in all patients (Mann-Whitney U-test, P < 0.0001) and were correlated inversely with age (Spearman’s rank correlation coefficient r = −0.65, P = 0.01). In summary, our systematic cross-sectional analysis of HSP-ZFYVE26 patients across a wide age-range, delineates core clinical, neuroimaging and molecular features and identifies markers of disease severity. These results raise awareness to this rare disease, facilitate an early diagnosis and create clinical trial readiness.
Online verfügbar: 31. Oktober 2022, Artikelversion: 21. Januar 2023
Gesehen am 26.03.2024